1986
DOI: 10.3801/iafss.fss.1-75
|View full text |Cite
|
Sign up to set email alerts
|

Upward Turbulent Flame Spread

Abstract: Mechanisms and rates of upward spread of turbulent flames along thermally thick vertical sheets are considered for both noncharring and charring fuels. By addressing the time dependence of the rate of mass loss of the burning face of a charring fuel, a linear integral equation of the Volterra type is derived for the spread rate. Measurements of spread rates, of flame heights and of surface temperature histories are reported for polymethylmethacrylate and for Douglas-fir particle board for flames initiated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
1
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(85 citation statements)
references
References 10 publications
(10 reference statements)
3
79
1
2
Order By: Relevance
“…Significant experimental research has already been conducted on flame spread in the vertical direction over homogeneous sheets of PMMA. Vertical flame spread presents one of the most dangerous fire hazards because the natural buoyancy allows for concurrent flame propagation and accelerating flame spread [22]. Drysdale and MacMillan studied effects of fuel orientation on the flame spread rate, and found substantially higher velocities as the angle of orientation approached the vertical [23].…”
Section: Previous Research On Upward Flame Spreadmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant experimental research has already been conducted on flame spread in the vertical direction over homogeneous sheets of PMMA. Vertical flame spread presents one of the most dangerous fire hazards because the natural buoyancy allows for concurrent flame propagation and accelerating flame spread [22]. Drysdale and MacMillan studied effects of fuel orientation on the flame spread rate, and found substantially higher velocities as the angle of orientation approached the vertical [23].…”
Section: Previous Research On Upward Flame Spreadmentioning
confidence: 99%
“…Initially, experimentalists simply took the flame height by eying an appropriate value (occasionally from video footage) [10][11][12][13]. In 1995, Audouin et al developed an image processing technique for pool fires where they averaged 160 images and obtained a flame presence probability [14].…”
Section: Flame Spread Modelsmentioning
confidence: 99%
“…Brehob et al [8] suggested another form for the correlation of w q ′ ′ & with height based on the data reported by Quintiere et al [7] and Kim [9], viz. [11] 30 Delichatsios and Delichatsios [12] 25 Delichatsios and Chen [13] 25…”
Section: Previous Experimental Investigationsmentioning
confidence: 99%
“…However, to simplify the problem, most of these models [9][10][11][12][13][14][15][16][17][18] assume that " w q & is constant over the preheating region, becoming zero at heights above X f . Saito et al [9] took 25 kW/m 2 as the constant heat flux exposed to which mass loss rate was obtained for their steady-state model. Good consistency has been shown with their PMMA flame spread rate measurement.…”
Section: Averaged Heat Flux Used In Upward Flame Spread Modellingmentioning
confidence: 99%
“…These correlations are based on test data like the Radiant Panel Rate of Flame Spread Test [26]. Other experimental correlations are developed from test data by Saito et al [27,28], Delichatsios et al [29], Quintiere and Harkleroad [30], Brehob and Kulkarni [31], and many other researchers; additional reviews are given by Joulain [32] and Brehob et al [33]. Given the extensive amount of available data, these correlations work well for most materials that are tested.…”
Section: Referencementioning
confidence: 99%